(untitled) (Web of Teachers: Inderscience Research, 2025)
Currently, a theory has been formed that with a change in the pH of the oral mucosa in the alkaline direction, the content of phosphate and bicarbonate ions in the oral mucosa increases, which increases the risk of stone formation in the oral mucosa. It has also been proven that when the protein composition of the oral mucosa changes, the probability of stone formation in the oral mucosa increases. Molar disease of the oral mucosa is one of the most common among other diseases of the mucous glands, the frequency of which ranges from 46% to 77%. Therefore, the study of this topic remains relevant today.